A EXPERIMENTAÇÃO NO ENSINO DE CIENCIAS: desafios e pespectivas de alunos e professores no processo ensino aprendizagem em Breves-Pará - MERCÊS, Paulo Santana das (2024)
The present research work has for objectives to analyze the process of the experimentation returned to the teaching of Sciences inside of the school context in the municipal district of Abbreviations, state of Pará. The work analyzes the teachers' action and students of the public net of teaching with returned focus the pedagogic practices used by the educators of sciences in groups from 6 to the 9 year of the fundamental teaching. The even search to do a reflection of the teacher's illustration inside of that process, since he should be the main responsible instrument for using of the pedagogic practical best similar of contributing in a satisfactory way with the process of the students' formation. The theoretical fundamentação of the work leans on in the reading of scientific goods, published concerning the theme of the experimentation inside of the education process returned to the teaching of sciences. The work also leans on in researches of interviews accomplished with students and educators. The used questionnaires were applied after the use of some experiments in classroom that you/they exemplify and they explain, mainly to the students that it is the experimentation in classroom. The work here presented has as main objective to emphasize them you practice returned the experimentation in the teaching of sciences, to clean the practices used by the teacher, besides verifying the performance of his/her student point of view about the use of experiments in classroom with focus in the relationship teaching learning.